Xerostomia and medications among 32-year-olds - THOMSON, WILLIAM MURRAY (2006)
OBJECTIVE: To describe the prevalence and associations of xerostomia among adults in their early thirties, with particular attention to medication exposure as a putative risk factor. MATERIAL AND METHODS: The prevalence and associations of xerostomia were investigated among 32-year-old participants in a long-standing prospective cohort study. Some 950 individuals were assessed at ages 26 and 32 years, with medications being recorded on both occasions. RESULTS: The prevalence of xerostomia was 10.0% (with no apparent gender difference), and was significantly higher among those taking antidepressants (odds ratio =4.7), iron supplements (OR =4.1) or narcotic analgesics (OR =2.4). Those taking antidepressants at both ages 26 and 32 years had 22 times the odds of reporting xerostomia. CONCLUSION: Xerostomia may be a problem for a sizeable minority of young adults.